Avatrombopag for the treatment of thrombocytopenia induced by chemotherapy in patients with solid tumors: A multicenter, open-label, single-arm trial - Cui, Yayun; He, Yifu; Hu, Changlu; Tu, Congyin; Huang, Jin; Zhu, Xiaofeng; Zang, Chunbao; Ding, Kaiyang; Zhan, Bihong; Zhao, Yufei; Qian, Liting (Frontiers in Pharmacology, 2022)
Objective: To explore the effect and safety of avatrombopag for chemotherapy-induced thrombocytopenia (CIT). Methods: This multicenter, open-label, single-arm trial enrolled CIT patients in eight centers from October 2020 to April 2021. The participants received avatrombopag tablets 60 mg once a day for 5-10 days. The main endpoint was the proportion of patients with platelet count ≥100×109/L or increased by ≥50×109/L or increased by ≥100% in the cycle after the start of treatment. Results: Seventy-four participants were enrolled with a mean age of 59.8±11. 62.2% were males. The cumulative effective rate (any criteria) was 70.3% at four weeks. 42 (56.8%) achieved platelet count ≥100×109/L, 44 (59.5%) increased by ≥50×109/L, and 27 (36.5%) increase by >100% from baseline. The duration of grade III and IV platelet reduction was 4.2±5.3 days. The time of PLT recovery to ≥75×109/L was 9.4±6.6 days. The time of PLT recovery to ≥100×109/L was 10.2±6.4 days. The platelet count nadir was 57.9±45.3×109/L. The most common adverse events were nausea (8.1%), fatigue (5.4%), and abdominal pain (1.4%). There were no cases of fever, headache, or peripheral edema. Conclusion: Although it was a single-arm trial without a control group, the application of avatrombopag in patients with CIT can increase the platelet count of the patients compared with baseline. Avatrombopag is safe and tolerable.